PENGARUH DELEGASI, OTORITAS, TANGGUNG JAWAB TERHADAP KINERJA PEGAWAI - Yolanda Oktarina; Hafidz Aima; Lusiana Lusiana; Silvia Sari; Rafnelly Rafk; Nofriadi Nofriadi (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
Employee performance plays an important role in the success and sustainability of the company. Effective management of employees is the key to achieving organizational goals, and factors affecting employee performance have become a major concern in human resource management. Although many studies have been conducted with respect to these factors, there are variations in results and findings. And those who study the factors of delegation, authority and responsibility for employee performance have not been many. So the title of this study is to study the Influence of Delegation, Authority, Responsibility on Employee Performance. This study uses a survey method of a sample of employees from various levels of hierarchy in Agency "X". The data collected is then analyzed using statistics i.e. by multiple regression analysis. The results showed that a higher level of delegation from superiors had a positive impact on employee performance. It was also found that clear authority and well-defined responsibilities contributed positively to employee performance. It can be concluded that the independent variables tested, namely delegation, authority, and responsibility, have a significant influence on the performance of employees in organization "X". Furthermore, policies and practices that support more effective and efficient management of human resources, including management training that understands the importance of delegation and the granting of appropriate authority, can be applied to the organization of "X" and other organizations.